CRITICAL REVIEW: IS RELIGIOUSITY AN IMPORTANT DETERMINANT ON MUSLIM CONSUMER BEHAVIOR IN MALAYSIA - Fasa, Muhammad Iqbal (IJRDO - Journal of Applied Management Science, 2016)
In a constantly changing and increasingly globalized world, the construct ofculture and subculture have become increasingly central to the consumer behaviorliterature. Religion still plays a significant role in influencing social and consumerbehavior. Religious belief is a significant factor in influencing consumptionbehavior because by the rules and taboos it inspires. Furthermore, religiosityrepresents an inherent human value which tends stable over a fairly long period oftime, and finally, many elements of religiosity are observable, and therefore ofpragmatic value to marketers (Khraim, 2010).Islam is a religion that guides Muslims in every aspect of life, not just inspecific acts of worship. For instance, in the Quranic verse, Al Isra’:26-27, Allahcommands Muslims not to consume or spend extravagantly, but to spend in a wayof Allah. Some other guidance which have been provided for by Islam are howand what to trade, how to interact with others and what can be consumed. Eatingand drinking are strictly followed according to the Islamic rules in the everydaylife of the Muslim society. But these norms however vary between differentreligious faiths and degree of observation.This discussion note provides comments on the issue, in particular the oneunder the notion of muslim consumer behavior in Malaysia written by Bro SyedShah Alam, Bro Rohani Mohd, and Bro. Badrul Hisham.